2020
DOI: 10.1530/rep-19-0562
|View full text |Cite
|
Sign up to set email alerts
|

Expression and steroid hormone regulation of TETs and DNMTs in human endometrium

Abstract: DNA methyltransferases (DNMTs) and ten-eleven translocation proteins (TETs) facilitate methylation and hydroxymethylation of DNA, respectively. DNMTs are widely studied with conflicting results on their regulation in the endometrium. While the role of TETs in the endometrium remains relatively unexplored. Deregulated expression of TETs and DNMTs are associated with endometrial pathologies. The aim of this study is to characterize the temporal TET expression in endometrium and to determine the hormonal regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…TET1 protein expression parallels the gene expression and is significantly downregulated when treated with estrogen-progesterone for 72 hours. According to the results of our previous study, TET1 mRNA was upregulated during the mid-secretory phase in healthy endometrial tissues and in response to progesterone treatment in epithelial cells, in vitro ( 29 ). The decreased protein expression during 72 hours of estrogen-progesterone treatment, suggests a potential aberrant regulation of TET1 in AN3 cells.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…TET1 protein expression parallels the gene expression and is significantly downregulated when treated with estrogen-progesterone for 72 hours. According to the results of our previous study, TET1 mRNA was upregulated during the mid-secretory phase in healthy endometrial tissues and in response to progesterone treatment in epithelial cells, in vitro ( 29 ). The decreased protein expression during 72 hours of estrogen-progesterone treatment, suggests a potential aberrant regulation of TET1 in AN3 cells.…”
Section: Discussionmentioning
confidence: 85%
“…Gene expression analysis was done using the comparative CT method (ΔΔCT method) ( 35 ). All the results were normalized to the geomeans of the three reference genes- YWHAZ, RPL13a and RPLO as described previously ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…In in-vitro experiments, treatment of endometrial epithelial cells with progesterone induced TET1 , TET2 , and TET3 expression, and estradiol plus progesterone treatment increased the expression of TET3. Experiments on stromal cells confirmed estradiol-induced TET1 expression [ 63 , 103 ]. A study by Ciesielski et al, showed a decreased expression of TET1 and TET2 in endometrial cancer [ 92 ].…”
Section: Role Of Tet Enzymes In Uf Developmentmentioning
confidence: 99%
“…2 ). It has been recently reported that estradiol induces the expression of DNMT1 and DNMT3b in cell cultures of immortalized stromal and epithelial endometrial cells, respectively, while estradiol and progesterone decrease the expression of DNMT1 in the stromal cells [ 89 ].
Fig.
…”
Section: Dna Methylationmentioning
confidence: 99%
“…In vitro treatments with progesterone induce TET1 , TET2, and TET3 expression in endometrial epithelial cells and estradiol plus progesterone treatments increase the expression of TET3 in the same cell type, while estradiol induces the expression of TET1 in stromal cells. Interestingly, all three TET proteins were detected in both epithelium and stroma throughout the endometrial cycle [ 89 ]. These studies suggest that sex hormones regulate the expression of MBD2 and TET genes in a dynamic and cell-specific manner in the human endometrium.…”
Section: Dna Methylationmentioning
confidence: 99%